The survey of Object-Related Negativity Evoked Potential in Concurrent Sound Segregation - Nasrin Gohari; Zahra Hosseini-Dastgerdi (Vesnu Publications, 2021)
Perception of concurrent sounds such as speech in the presence of noise is one of the auditory challenges in many disorders such as auditory processing disorders, hearing loss, learning disabilities, autism, etc. in children, adults, and the elderly. Objective examination of concurrent sound perception is possible using object-related negativity (ORN) electrophysiological assessments. This wave can be recorded in the range of N1 and P2 late latency responses (LLR). The stimuli used to obtain this wave are dichotic pitch, spatial differences, simulated echoes, asynchronous  at the onset, and mistuned harmonics. This wave can be detected in the frontocentral part of the brain, and since it has not yet been completely studied in various disorders, we recommend it in objective studies in future research as well as clinical and rehabilitation monitoring.